Christopher Pizzino. Arresting Development: Comics at the Boundaries of Literature. Austin: U of Texas P, 2016. - Katlin M Sweeney (Studies in 20th & 21st Century Literature, 2017)
Review of Christopher Pizzino. Arresting Development: Comics at the Boundaries of Literature. Austin: U of Texas P, 2016.
Keywords: comics studies; the graphic novel; marginalized comics; coming of age; autoclasm